The synthesis and characterization N‐methyl‐3‐phenyl‐norbornan‐2‐amine (Camfetamine™). Issue 4 (28th February 2012) - Kavanagh, Pierce; Angelov, Daniel; O'Brien, John; Power, John D.; McDermott, Seán D.; Talbot, Brian; Fox, John; O'Donnell, Cora; Christie, Rachel
<x xml:space="preserve">Abstract</x> N‐Methyl‐3‐phenyl‐norbornan‐2‐amine (N‐methyl‐3‐phenylbicyclo[2.2.1]heptan‐2‐amine, Camfetamine™) is available from a number of online legal highs/research chemicals' vendors. Although it was developed as an analeptic by Merck in the early 1960s, it was never commercialized. However, the Association of Independent Research Chemical Retailers (AIRCR), an umbrella organization for a number of online vendors, has redeveloped it for use as a recreational drug. N‐Methyl‐3‐phenyl‐norbornan‐2‐amine is closely related to fencamfamine which has been widely used as a central nervous system (CNS) stimulant and appetite suppressant. In this paper we describe the synthesis of N‐methyl‐3‐phenyl‐norbornan‐2‐amine, its characterization and interpretations of its electron impact, and electrospray ionization mass spectra. Copyright © 2012 John Wiley & Sons, Ltd.